Mid infrared digital holography and terahertz imaging - Locatelli, Massimiliano (Premio Tesi di Dottorato, 2014)
Mid IR and Far IR (THz) regions have been attracting a continuously growing interest, especially for imaging applications. Mid IR imaging systems are widespread in the military, security and medical fields and are, consequently, in continuous development. Even greater expectation is placed on THz imaging techniques, because of the well-known capacity of THz radiation to penetrate many common materials and to provide important spectroscopic information about various strategic stuffs. In this scenario Digital Holography, a quite recent interferometric imaging technique, is proving to be mature enough to play a key role among the other imaging techniques, both in the Mid IR and in the Far IR.